Atypical Carboxysome Loci: JEEPs or Junk? - , USF Genomics Class 2020, USF Genomics Class 2021; Sutter, Markus; Kerfeld, Cheryl A.; Scott, Kathleen M. (Frontiers in Microbiology, 2022)
Carboxysomes, responsible for a substantial fraction of CO2 fixation on Earth, are proteinaceous microcompartments found in many autotrophic members of domain Bacteria, primarily from the phyla Proteobacteria and Cyanobacteria. Carboxysomes facilitate CO2 fixation by the Calvin-Benson-Bassham cycle, particularly under conditions where the CO2 concentration is variable or low, or O2 is abundant. These microcompartments are composed of an icosahedral shell containing the enzymes RubisCO (ribulose 1,5-carboxylase/oxygenase) and carbonic anhydrase. They function as part of a CO2 concentrating mechanism, in which cells accumulate HCO3- in the cytoplasm via active transport, HCO3- enters the carboxysomes through pores in the carboxysomal shell proteins, and carboxysomal carbonic anhydrase facilitates the conversion of HCO3- to CO2, which RubisCO fixes. Two forms of carboxysomes have been described: α-carboxysomes and β-carboxysomes, which arose independently from ancestral microcompartments. The α -carboxysomes present in Proteobacteria and some Cyanobacteria have shells comprised of four types of proteins (CsoS1 hexamers, CsoS4 pentamers, CsoS2 assembly proteins, and CsoSCA carbonic anhydrase), and contain form IA RubisCO (CbbL and CbbS). In the majority of cases, these components are encoded in the genome near each other in a gene locus, and transcribed together as an operon. Interestingly, genome sequencing has revealed some α -carboxysome loci that are missing genes encoding one or more of these components. Some loci lack the genes encoding RubisCO, others lack a gene encoding carbonic anhydrase, some loci are missing shell protein genes, and in some organisms, genes homologous to those encoding the carboxysome-associated carbonic anhydrase are the only carboxysome-related genes present in the genome. Given that RubisCO, assembly factors, carbonic anhydrase, and shell proteins are all essential for carboxysome function, these absences are quite intriguing. In this review, we provide an overview of the most recent studies of the structural components of carboxysomes, describe the genomic context and taxonomic distribution of atypical carboxysome loci, and propose functions for these variants. We suggest that these atypical loci are JEEPs, which have modified functions based on the presence of Just Enough Essential Parts.